Continuously feeding fenton sludge into anaerobic digesters: Iron species change and operating stability. (1st November 2022) - Sun, Ye; Wang, Mingwei; Liang, Lianfu; Sun, Cheng; Wang, Xuepeng; Wang, Zhenxin; Zhang, Yaobin
Highlights: Fenton sludge as an Fe(III) source of dissimilatory iron reduction improved anaerobic treatment. Fenton sludge could be consumed during anaerobic digestion to a certain extent. Continuously feeding Fenton sludge did not deteriorate anaerobic treatment. Iron content in the digester decreased when stopping feeding Fenton sludge. Feeding Fenton sludge increased the electron transfer capacity of microorganisms. Abstract: Fenton sludge generated from the Fenton process contains a large number of ferric species and organic pollutants, which need to be properly treated before discharge. In this study, Fenton sludge as an Fe(III) source for dissimilatory iron reduction (DIR) was continuously added with increasing dosage into an anaerobic digester to enhance the treatment. Results showed continuously feeding Fenton sludge to the anaerobic digester did not deteriorate the performance and increased methane production and COD removal rate by 2.2 folds and 14.0%, respectively. The Fe content of sludge in the digester increased from 40.25 mg/g (dry weight) to 131.53 mg/g after continuously feeding for 77days, and then declined to 109.17 mg/g when the feeding was stopped. Mass balance analysis showed that 20.5 to 48.4% of Fe in the Fenton sludge was released to the effluent. After experiment, the ratio of reducible Fe species to the total Fe was 75.1%, which maintained the high activity in DIR. Microbial community analysis showed that iron-reducing bacteria were enriched with the addition of Fenton sludge and the sludge in the digester had a higher conductivity and capacitance to strengthen the electron transfer of DIR. All results suggested that feeding Fenton sludge into anaerobic digesters was a feasible method to dispose of Fenton sludge as well as to enhance the performance of anaerobic digestion. Graphical abstracts: Image, graphical abstract